MnO2-loaded porous carbon-based electrode material as well as preparation method and application thereof
By using the molten salt method to prepare porous carbon materials and load MnO2 in supercapacitors, the problem of insufficient energy density of existing supercapacitors is solved, the specific capacitance and electrochemical performance are significantly improved, and solid waste resource utilization and green and environmentally friendly production process are realized.
Patent Information
- Application Number
- CN202510140637.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-04-18
AI Technical Summary
The insufficient energy density of existing supercapacitors limits its commercialization process, and the specific capacitance performance of porous carbon materials is difficult to significantly improve.
Porous carbon materials were prepared by molten salt method, and medium and low temperature coal asphalt was used as carbon precursor and mixed salts of carbonate and chloride as activator to form porous carbon materials with a high specific surface area, and MnO2 was uniformly loaded on the surface of the porous carbon materials by impregnation and precipitation method.
It significantly improves the specific capacitance performance of porous carbon materials, improves the power density and electrochemical performance of supercapacitors, and realizes the resource utilization of solid waste. This method is green and environmentally friendly and has a high recovery rate.
Smart Images

Figure CN119852099A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional materials and electrochemical technology, and specifically relates to a MnO2 loaded porous carbon-based electrode material and a preparation method and application thereof. Background Art
[0002] Supercapacitors, as a cutting-edge energy storage device, show great potential in the field of energy storage due to their excellent cycle stability and fast charge and discharge capabilities. However, their insufficient energy density has become a key factor restricting their commercialization process. Supercapacitors are a new type of energy storage device with excellent properties such as high power density, long cycle life and fast charge and discharge. They are widely used in electric vehicles, smart grids and portable electronic devices. The performance of supercapacitors depends largely on the properties of their electrode materials.
[0003] At present, the commonly used electrode materials for supercapacitors mainly include carbon-based materials, metal oxides, conductive polymers and hybrid materials. As a type of carbon-based material, porous carbon materials dominate the field of electrode materials due to their high specific surface area, fine pore structure and excellent conductivity. However, due to their single energy storage mechanism and relatively low apparent density, it is difficult for porous carbon materials to achieve a significant leap in specific capacitance performance.
[0004] The prior art generally adopts KOH chemical activation method to prepare porous carbon materials. However, the chemical reagent KOH needs to be used in the activation process, resulting in low porosity of the prepared porous carbon material, thereby making the specific capacitance performance of the porous carbon material poor. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a MnO2 loaded porous carbon-based electrode material and a preparation method and application thereof.
[0006] During the preliminary research, the present invention found that when porous carbon is prepared by the molten salt method, with the assistance of molten salt, the carbon precursor tends to produce richer pore structures and / or specific morphologies during the carbonization process. This is because the synthesis of carbon materials by molten salt is mainly based on the electrochemical redox reaction of electrode materials and / or electrolytes. The electrodeposition of carbon materials can be achieved by electrolysis of carbonates, and the microstructure of the deposited carbon is directly affected by the electrochemical parameters and the composition of the molten salt. The porous carbide-derived carbon prepared by removing non-carbon atoms from the carbon precursor can be used in supercapacitors due to its customized pore size, morphology and microstructure, which is beneficial to improving the specific capacitance performance of porous carbon materials. Compared with other transition metal oxides / hydroxides, MnO2 has a high theoretical specific capacitance of 1370F g -1, low cost and environmentally friendly. In addition, MnO2 exhibits higher specific capacitance and energy density than other metal oxides.
[0007] The present invention is based on medium and low temperature coal tar pitch as raw material, uses coal tar pitch as the precursor of porous carbon material, adopts molten salt method to mix salt with coal tar pitch, uses the gas generated by pyrolysis of carbonate at high temperature to make pores in carbon material, and at the same time, uses Cl in chloride salt to generate pores in carbon material. - At high temperature, it adheres to the porous carbon material to prepare a porous carbon material with high specific capacitance performance; then the porous carbon material is added into a solution containing potassium permanganate by the impregnation precipitation method, and then a reducing agent is added, and the generated MnO2 is evenly loaded on the surface of the porous carbon material to form a composite structure of the porous carbon material loaded with MnO2; the high specific capacitance characteristics of MnO2 are used to further improve the electrochemical performance of the electrode material.
[0008] The first object of the present invention is to provide a method for preparing a MnO2-loaded porous carbon-based electrode material, comprising the following steps:
[0009] Step 1: Use coal tar pitch as a carbon precursor, use a mixed salt of carbonate and chloride as an activator, mix the coal tar pitch with the activator, and use a molten salt method to pyrolyze the coal tar pitch at high temperature to convert it into a carbon material. The activator creates pores in the carbon material. At the same time, the Cl in the chloride salt - Attached to the carbon material to obtain a porous carbon material.
[0010] It should be noted that coal tar is a carbon-rich organic material with a wide range of sources and low cost, and is suitable as a precursor for porous carbon materials. Coal tar can be converted into carbon materials during high-temperature pyrolysis, and its high carbon content is conducive to the formation of a highly conductive structure. The present invention uses coal tar as a carbon precursor, and a mixed salt of carbonates and chlorides as an activator, and utilizes carbonates and chlorides to react with coal tar at high temperatures; a portion of carbonates is pyrolyzed at high temperatures to form metal oxides and CO2, and the generated CO2 continues to react with carbon materials at high temperatures to produce CO; another portion of carbonates reacts with carbon materials at high temperatures to generate K and CO, and a portion of carbon materials reacts with K2O to generate K and CO; the gas generated by activation is difficult to be released from the matrix in time, which will cause the matrix to expand or even bubble. When the pressure reaches a certain value, the bubbles are destroyed, and holes and flaky wall structures are generated on the surface of the carbon material to obtain a porous carbon material; at the same time, the Cl in the chloride salt - It adheres to the porous carbon material at high temperature and generates chemical energy under the action of external electrical energy to improve the redox ability of the electrode material.
[0011] It should also be noted that the present invention increases the performance of porous carbon by using the properties of different salts. The present invention utilizes CO3 in carbonates to 2-Ions can increase the C=O functional group in the carbon precursor at high temperature, while the Cl in the chloride salt - The redox capacity can be increased, thereby increasing the pseudocapacitance ratio; preferably, the activator is a mixed salt of chloride and carbonate, and the mass of the carbonate is 40% to 60% of the mass of the activator.
[0012] When the mass of the activator is more than 3 times the mass of coal tar, on the one hand, it is easy to cause the destruction of the carbon skeleton structure of the porous carbon material; on the other hand, the excess activator and the carbon precursor reduce the recovery rate through the activation reaction, which will also lead to poor performance tests of the carbon material. If the mass of the activator is less, it is easy to cause the number of pores in the porous carbon material to decrease, and a large amount of carbon precursor is wasted without reaction. Preferably, the mass of the activator is 1 to 5 times the mass of the coal tar; more preferably, the mass of the activator is 3 times the mass of the coal tar.
[0013] When the pyrolysis temperature is lower than 700°C, the K2CO3 in the activator will not react completely, resulting in a large number of defects; and when the pyrolysis temperature is higher than 900°C, the carbon precursor will be severely damaged, resulting in a large number of carbon skeletons collapsing, thereby reducing the performance of the material. Preferably, the pyrolysis temperature of the molten salt method is 700°C to 900°C; more preferably, the pyrolysis temperature of the molten salt method is 700°C.
[0014] Step 2: Using an impregnation precipitation method, the porous carbon material and potassium permanganate solution are mixed, and under the action of a reducing agent, the potassium permanganate is reduced to MnO2 and loaded on the porous carbon material to obtain a porous carbon-based electrode material loaded with MnO2.
[0015] It should be noted that MnO2 has a high theoretical specific capacitance and excellent electrochemical properties, and can significantly improve the specific capacitance and electrochemical properties of porous carbon materials. The present invention immerses the porous carbon material in a potassium permanganate solution, which is an excellent oxidant, and then adds methanol as a reducing agent to generate MnO2 on its surface; at the same time, under the action of the reducing agent, the potassium permanganate in the solution is reduced to MnO2 to form a MnO2 deposition layer on the porous carbon surface. The present invention utilizes Mn in MnO2 4+ The redox property of the electrode is improved by converting chemical energy into electrical energy to increase the proportion of pseudocapacitance of the electrode, and the specific capacitance of the electrode is increased by improving the redox ability of the capacitor. Preferably, the reducing agent is methanol or sodium borohydride.
[0016] Preferably, 0.125 mol to 0.25 mol of MnO2 is loaded per 1 g of the porous carbon material.
[0017] Preferably, the dosage ratio of the reducing agent to the potassium permanganate solution in the potassium permanganate solution is 4 mL to 8 mL: 0.5 mmol to 1 mmol.
[0018] The second object of the present invention is to provide a MnO2 loaded porous carbon-based electrode material obtained by the above preparation method.
[0019] The third object of the present invention is to use the above-mentioned MnO2 loaded porous carbon-based electrode material in the preparation of a supercapacitor, wherein the MnO2 loaded porous carbon-based electrode material is used as an electrode in a supercapacitor.
[0020] Preferably, the supercapacitor is prepared by the following steps:
[0021] S1. Mix the loaded MnO2 porous carbon-based electrode material and the conductive agent, then add the binder, and continue to grind and mix until it becomes a black viscous state to obtain an active slurry.
[0022] S2. Apply the active slurry on a current collector and dry it to form an active material layer on the current collector to obtain an electrode sheet.
[0023] S3. Dissolve KOH in water to prepare an electrolyte.
[0024] S4. Place the electrode sheet in the electrolyte to form a supercapacitor.
[0025] Preferably, the dosage ratio of the MnO2-loaded porous carbon material, the conductive agent and the binder is 60 g to 65 g: 7 mg to 8 mg: 5 μL.
[0026] Preferably, the concentration of the electrolyte is 5 mol / L to 8 mol / L.
[0027] Preferably, the current collector is nickel foam; and the thickness of the current collector is 1 mm to 3 mm.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The present invention uses coal tar as a carbon precursor, a mixed salt of carbonate and chloride as an activator, and a molten salt method to cause the carbonate to undergo a pyrolysis reaction to form metal oxides and CO2; and under the action of chloride, the carbonate and the carbon material undergo an oxidation-reduction reaction to form CO2 and CO gas; the gas generated by activation is difficult to be released from the matrix in time, which will cause the matrix to expand or even bubble. When the pressure reaches a certain value, the bubbles are destroyed, and holes and flaky wall structures are generated on the surface of the carbon material. At the same time, the present invention uses different types of salts to add different properties to the porous carbon, using the CO3 in the carbonate to 2- Ions can increase the C=O functional groups in the carbon precursor at high temperatures, and can also increase the carbonization degree of the graphite of the carbon material. -It can increase its redox capacity and thus increase its pseudocapacitance ratio, thereby improving the power density and electrochemical performance of the supercapacitor.
[0030] The present invention adopts an impregnation precipitation method to mix the porous carbon material with potassium permanganate, and under the action of a reducing agent, the potassium permanganate is reduced to MnO2 and uniformly loaded on the surface of the porous carbon material, providing more active sites; at the same time, the present invention utilizes Mn in MnO2 to 4+ The redox property of MnO2 not only increases the capacitance of the material, but also increases the cycle stability of the electrode, thus extending the service life of the supercapacitor.
[0031] The present invention is based on medium and low temperature coal tar pitch as raw material, uses coal tar pitch as carbon material precursor, and adopts molten salt method to prepare porous carbon material with high specific surface area; then adopts impregnation precipitation method to uniformly load MnO2 on the surface of porous carbon material to form high-performance MnO2 loaded porous carbon material; the material has high specific surface area, high conductivity and excellent electrochemical properties, and is applied in the field of supercapacitors to significantly improve the specific capacitance performance of supercapacitors and realize the resource utilization of solid waste.
[0032] The present invention adopts the molten salt method, uses salt as an activator, and does not use chemical reagents. Compared with the KOH chemical activation method, it is green and environmentally friendly; and in the post-treatment process, only water washing is required to remove the activator, and the recovery rate of the prepared porous carbon is higher. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is the XRD spectrum of the MnO2 loaded porous carbon-based electrode material prepared in Examples 1 to 3 of the present invention.
[0034] Figure 2 This is the SEM image of the PCS prepared in Comparative Example 1 of the present invention.
[0035] Figure 3 This is the SEM image of PCS-MnO2 prepared in Example 1 of the present invention.
[0036] Figure 4 This is the SEM image of PCS-MnO2 prepared in Example 1 of the present invention.
[0037] Figure 5 CV curves of PCS-MnO2 prepared in Example 1 of the present invention and PCS prepared in Comparative Example 1.
[0038] Figure 6 Constant current charge and discharge curves of PCS-MnO2 prepared in Example 1 of the present invention and PCS prepared in Comparative Example 1.
[0039] Figure 7 The specific capacitance of PCS-MnO2 prepared in Example 1 of the present invention and PCS prepared in Comparative Example 1 are obtained through constant current charge and discharge curves.
[0040] Figure 8 EIS spectra of PCS-MnO2 prepared in Example 1 of the present invention and PCS prepared in Comparative Example 1.
[0041] Fig. 9 This is a CV comparison diagram of PCS-MnO2 prepared in Example 1 of the present invention at different scan rates.
[0042] Fig.10 This is a diagram showing the pseudocapacitance ratio of PCS-MnO2 prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0043] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings.
[0044] In the description of the present invention, unless otherwise specified, all reagents used are commercially available and all methods used are conventional techniques in the art.
[0045] Example 1
[0046] This embodiment provides a method for preparing a MnO2 loaded porous carbon-based electrode material.
[0047] Step 1: Preparation of porous carbon material:
[0048] 1.1) Sieve the coal tar pitch through a 120-mesh sieve to obtain sieved coal tar pitch.
[0049] 1.2) Weigh 1.2 g of K2CO3 and 1.8 g of KCl, place in a drying oven at 105°C and dry for 12 h to obtain a mixed salt.
[0050] 1.3) Put 1g of coal tar pitch and 3g of mixed salt into a mortar and grind them thoroughly for 30 minutes to obtain a carbon salt mixture.
[0051] 1.4) The carbon salt mixture was placed in a 10 mL porcelain boat and placed in a tube furnace. The heating rate of the tube furnace was adjusted to 5 °C / min under a N2 atmosphere, and heated to 700 °C. The temperature was kept for 2 h to obtain a porous carbon loaded with salt.
[0052] 1.5) The salt-loaded porous carbon was placed in a 200 mL beaker, and then 100 mL of deionized water was added, and the sample was oscillated in an ultrasonic oscillator for 1 hour for washing; the water of the oscillated sample was then filtered out by a vacuum filtration instrument, and then 100 mL of deionized water was added after taking it out, and the sample was placed in an ultrasonic oscillator for 1 hour for ultrasonication. The washing process was repeated 3 times, and finally the washed sample was placed in a vacuum drying oven and dried at a drying temperature of 105°C for 12 hours to obtain a porous carbon material.
[0053] Step 2: Preparation of MnO2-loaded porous carbon-based electrode materials:
[0054] 2.1) Weigh 0.1185 g of KMnO4, add it into 100 mL of deionized water, and stir for 10 min to obtain a KMnO4 aqueous solution.
[0055] 2.2) Use a rubber-tipped dropper to drop 6 mL of methanol into the KMnO4 aqueous solution and stir for 30 min to obtain a KMnO4 solution.
[0056] 2.3) Add 0.4 g of porous carbon material to the KMnO4 solution, put it into a heat-collecting constant temperature heating magnetic stirrer, and stir it at 70°C for 7 hours to obtain a MnO2 loaded porous carbon-based electrode material, recorded as PCS-MnO2.
[0057] Example 2
[0058] This embodiment provides a method for preparing a MnO2 loaded porous carbon-based electrode material.
[0059] Step 1: Preparation of porous carbon material:
[0060] 1.1) Sieve the coal tar pitch through a 120-mesh sieve to obtain sieved coal tar pitch.
[0061] 1.2) Weigh 1.2 g of K2CO3 and 1.8 g of KCl, place in a drying oven at 105°C for 12 h to obtain a dry mixed salt.
[0062] 1.3) Put 1g of coal tar pitch and 3g of mixed salt into a mortar and grind them thoroughly for 30min to obtain a carbon salt mixture.
[0063] 1.4) The carbon salt mixture was placed in a 10 mL porcelain boat and placed in a tube furnace. The heating rate of the tube furnace was adjusted to 5 °C / min under a N2 atmosphere, and heated to 700 °C. The temperature was kept for 2 h to obtain a porous carbon loaded with salt.
[0064] 1.5) The salt-loaded porous carbon was placed in a 200 mL beaker, and then 100 mL of deionized water was added, and the sample was oscillated in an ultrasonic oscillator for 1 hour for washing; the water of the oscillated sample was then filtered out by a vacuum filtration instrument, and then 100 mL of deionized water was added after taking it out, and the sample was placed in an ultrasonic oscillator for 1 hour for ultrasonication. The washing process was repeated 3 times, and finally the washed sample was placed in a vacuum drying oven and dried at a drying temperature of 105°C for 12 hours to obtain a porous carbon material.
[0065] Step 2: Preparation of MnO2-loaded porous carbon-based electrode materials:
[0066] 2.1) Weigh 0.079 g of KMnO4, add it to 100 mL of deionized water, and stir for 10 min to obtain a KMnO4 aqueous solution.
[0067] 2.2) Use a rubber-tipped dropper to drop 4 mL of methanol into the KMnO4 aqueous solution and stir for 30 min to obtain a KMnO4 solution.
[0068] 2.3) Add 0.4 g of porous carbon material to the KMnO4 solution, put it into a heat-collecting constant temperature heating magnetic stirrer, and stir it at 70°C for 7 hours to obtain a MnO2 loaded porous carbon-based electrode material, recorded as PCS-MnO2.
[0069] The difference between this embodiment and embodiment 1 is:
[0070] The MnO2 loading amount in the MnO2 loaded porous carbon-based electrode material prepared in this embodiment is 0.79 g.
[0071] Example 3
[0072] This embodiment provides a method for preparing a MnO2 loaded porous carbon-based electrode material.
[0073] Step 1: Preparation of porous carbon material:
[0074] 1.1) Sieve the coal tar pitch through a 120-mesh sieve to obtain sieved coal tar pitch.
[0075] 1.2) Weigh 1.2 g of K2CO3 and 1.8 g of KCl, place in a drying oven at 105°C for 12 h to obtain a dry mixed salt.
[0076] 1.3) Put 1g of coal tar pitch and 3g of mixed salt into a mortar and grind them thoroughly for 30min to obtain a carbon salt mixture.
[0077] 1.4) The carbon salt mixture was placed in a 10 mL porcelain boat and placed in a tube furnace. The heating rate of the tube furnace was adjusted to 5 °C / min under a N2 atmosphere, and heated to 700 °C. The temperature was kept for 2 h to obtain a porous carbon loaded with salt.
[0078] 1.5) The salt-loaded porous carbon was placed in a 200 mL beaker, and then 100 mL of deionized water was added, and the sample was oscillated in an ultrasonic oscillator for 1 hour for washing; the water of the oscillated sample was then filtered out by a vacuum filtration instrument, and then 100 mL of deionized water was added after taking it out, and the sample was placed in an ultrasonic oscillator for 1 hour for ultrasonication. The washing process was repeated 3 times, and finally the washed sample was placed in a vacuum drying oven and dried at a drying temperature of 105°C for 12 hours to obtain a porous carbon material.
[0079] Step 2: Preparation of MnO2-loaded porous carbon-based electrode materials:
[0080] 2.1) Weigh 0.158 g of KMnO4, add it to 100 mL of deionized water, and stir for 10 min to obtain a KMnO4 aqueous solution.
[0081] 2.2) Use a rubber-tipped dropper to drop 8 mL of methanol into the KMnO4 aqueous solution and stir for 30 min to obtain a KMnO4 solution.
[0082] 2.3) Add 0.4 g of porous carbon material to the KMnO4 solution, put it into a heat-collecting constant temperature heating magnetic stirrer, and stir it at 70°C for 7 hours to obtain a MnO2 loaded porous carbon-based electrode material, recorded as PCS-MnO2.
[0083] The difference between this embodiment and embodiment 1 is:
[0084] The MnO2 loading amount in the MnO2 loaded porous carbon-based electrode material prepared in this embodiment is 1.185 g.
[0085] Example 4
[0086] This embodiment provides a method for preparing a MnO2 loaded porous carbon-based electrode material.
[0087] The difference between this embodiment and embodiment 1 is:
[0088] The amount of coal tar pitch used in this embodiment is the same as the mass of the mixed salt.
[0089] Example 5
[0090] This embodiment provides a method for preparing a MnO2 loaded porous carbon-based electrode material.
[0091] The difference between this embodiment and embodiment 1 is:
[0092] In this embodiment, the amount of coal tar pitch is twice the mass of mixed salt.
[0093] Example 6
[0094] This embodiment provides a method for preparing a MnO2 loaded porous carbon-based electrode material.
[0095] The difference between this embodiment and embodiment 1 is:
[0096] The amount of coal tar pitch used in this embodiment is 4 times the mass of the mixed salt.
[0097] Example 7
[0098] This embodiment provides a method for preparing a MnO2 loaded porous carbon-based electrode material.
[0099] The difference between this embodiment and embodiment 1 is:
[0100] The amount of coal tar pitch used in this embodiment is 5 times the mass of the mixed salt.
[0101] Comparative Example 1
[0102] This comparative example provides a method for preparing a porous carbon material.
[0103] 1.1) Sieve the coal tar pitch through a 120-mesh sieve to obtain sieved coal tar pitch.
[0104] 1.2) Weigh 1.2 g of K2CO3 and 1.8 g of KCl, place in a drying oven at 105°C for 12 h to obtain a dry mixed salt.
[0105] 1.3) Put 1g of coal tar pitch and 3g of mixed salt into a mortar and grind them thoroughly for 30min to obtain a carbon salt mixture.
[0106] 1.4) The carbon salt mixture was placed in a 10 mL porcelain boat and placed in a tube furnace. The heating rate of the tube furnace was adjusted to 5 °C / min under a N2 atmosphere, and heated to 700 °C. The temperature was kept for 2 h to obtain a porous carbon loaded with salt.
[0107] 1.5) The salt-loaded porous carbon was placed in a 200 mL beaker, and then 100 mL of deionized water was added, and the sample was oscillated in an ultrasonic oscillator for 1 hour for washing; the water of the oscillated sample was then filtered out by a vacuum filtration instrument, and then 100 mL of deionized water was added after taking it out, and the sample was placed in an ultrasonic oscillator for ultrasonication for 1 hour. The washing process was repeated 3 times, and finally the washed sample was placed in a vacuum drying oven and dried at a drying temperature of 105°C for 12 hours to obtain a porous carbon material, recorded as PCS.
[0108] Application Example 1
[0109] This application embodiment provides a method for preparing a supercapacitor.
[0110] 1.1) 60.8 g of the MnO2-loaded porous carbon-based electrode material prepared in Example 1 and 7.6 mg of the conductive agent acetylene black were put into a mortar and ground, and then 5 μL of the binder PTFE was added dropwise, and the grinding was continued for 30 min until it became a black viscous state to obtain an active slurry.
[0111] 1.2) Take 3 cm×3 cm nickel foam and put it into ethanol for ultrasonic treatment for 30 min. Then take it out and put it into acetone for ultrasonic treatment for 1 h. Then put it into a drying oven at 45° C. for 12 h to obtain pretreated nickel foam.
[0112] 1.3) Apply the active slurry on weighing paper and spread it evenly with a rolling pin. Then, place the pretreated nickel foam on the black slurry and cut it into a 1 cm×1 cm current collector layer using a square mold.
[0113] 1.4) Add ethanol to the current collector layer to moisten it, remove the weighing paper with tweezers, and then use a tablet press to press the current collector layer at 8 MPa to obtain an electrode sheet.
[0114] 1.5) Weigh 16.81 g of KOH solid and dissolve it in 50 mL of pure water. Stir for 2 h to obtain 6 mol / L KOH electrolyte.
[0115] 1.6) Use an electrode clamp to place the electrode sheet in the KOH electrolyte to form a supercapacitor.
[0116] Application Example 2
[0117] This application embodiment provides a method for preparing a supercapacitor.
[0118] This application example refers to the preparation method of application example 1, and uses the MnO2 loaded porous carbon-based electrode material prepared in example 2 to prepare the active slurry.
[0119] Application Example 3
[0120] This application embodiment provides a method for preparing a supercapacitor.
[0121] This application example refers to the preparation method of application example 1, and uses the MnO2 loaded porous carbon-based electrode material prepared in example 3 to prepare the active slurry.
[0122] Application Comparative Example 1
[0123] This application comparative example provides a method for preparing a supercapacitor.
[0124] This application comparative example refers to the preparation method of application example 1, and uses the porous carbon material prepared in comparative example 1 to prepare the active slurry.
[0125] Experimental testing
[0126] 1. XRD characterization
[0127] Figure 1 The XRD patterns of PCS-MnO2 prepared in Examples 1 to 3 are shown in Table 1. Figure 1 It can be seen that weaker graphite C(002) and C(100) crystal plane diffraction peaks appeared under the action of KCl and K2CO3, which may be due to the fact that MnO2 covered the surface of the porous carbon material and reduced the degree of graphitization. The diffraction peaks of birnessite phase MnO2 on (101), (006) and (002) crystal planes appeared at 19.1° and 37°, further confirming the formation of MnO2 phase, indicating that the present invention successfully prepared MnO2-loaded porous carbon-based electrode materials.
[0128] 2. SEM characterization
[0129] Figure 2 This is the SEM image of the PCS prepared in Comparative Example 1. Figure 2 It can be seen that the porous structure of PCS is clear, and the coal tar is modified by the mixed salt of KCl and K2CO3 at high temperature to form a porous carbon structure.
[0130] Figure 3 This is a SEM image of PCS-MnO2 prepared in Example 1. Figure 3 As shown, coal tar pitch is modified by a mixed salt of KCl and K2CO3 at high temperature. K2CO3 decomposes into K2O and CO2 at high temperature to initially form pores in the porous carbon. As the activation temperature increases, KCl and K2O further decompose to form K and CO, which cause secondary pore formation in the carbon source to form a porous carbon structure.
[0131] Figure 4 This is the SEM image of PCS-MnO2 prepared in Example 1. Figure 4 It can be seen that MnO2 is uniformly loaded on the porous carbon.
[0132] 3. Electrochemical test
[0133] The present invention utilizes Wuhan Coster electrochemical workstation to detect electrode performance, adopts a three-electrode system for testing, the counter electrode is a platinum electrode, the reference electrode is Hg / HgO, and the electrolyte is 6 mol / L KOH.
[0134] Figure 5 The CV curves of PCS-MnO2 prepared in Example 1 and PCS prepared in Comparative Example 1. By comparing the CV curves, it is found that at a scanning rate of 100 mV / s, the CV curve of PCS presents a preliminary non-rectangular shape; the CV curve of PCS-MnO2 gradually deepens the redox peak from -0.2V to 0.2V; this is because Mn 4+ and Mn3+ The redox reaction caused by the valence change between the two causes pseudocapacitance behavior. The present invention calculates the specific capacitance of PCS-MnO2 and PCS respectively through formula 1, the specific capacitance of PCS-MnO2 is 79.89F / g, and the specific capacitance of PCS is 75.48F / g; then the capacitance contribution of the surface capacitance control and diffusion control process of the electrode material is quantitatively analyzed according to formulas 2 and 3; the load of MnO2 increases the proportion of pseudocapacitance, and the specific capacitance increases due to the deepening of the redox peak.
[0135]
[0136] In formula 1, C p is the specific capacitance; A is the closed curve area of the CV curve; m is the mass of the active slurry; k is the scan rate.
[0137] i=k1v+k2v 1 / 2 Formula 2;
[0138]
[0139] Figure 6 The constant current charge-discharge curves of PCS-MnO2 prepared in Example 1 and PCS prepared in Comparative Example 1 are shown in FIG. Figure 6 As shown in the figure, the constant current charge-discharge curve of PCS-MnO2 deviates seriously from the isosceles triangle, indicating that PCS-MnO2 is mainly based on the pseudocapacitive energy storage mechanism, which is consistent with the CV curve analysis.
[0140] Figure 7 The specific capacitance of PCS-MnO2 prepared in Example 1 and PCS prepared in Comparative Example 1 obtained by constant current charge-discharge curve. According to the formula 4 of the constant current charge-discharge curve, the specific capacitance of PCS-MnO2 and PCS are 816.35F / g and 512.85F / g respectively, which are proportional to the integrated area of the CV curve. It also shows that using MnO2 as a load can effectively improve its electrochemical performance by improving its redox performance.
[0141]
[0142] In formula 4, C m is the specific capacitance, unit Fg -1 ; I is the test current of charge and discharge, unit is A; Δt is the discharge time, unit is s; m is the mass of active slurry, unit is g; Δv is the discharge voltage difference, unit is V.
[0143] Figure 8The EIS spectra of PCS-MnO2 prepared in Example 1 and PCS prepared in Comparative Example 1. From the comparison in the figure, it is found that the semicircle diameter of PCS in the high frequency region is also significantly smaller than the semicircle diameter of PCS-MnO2 in the high frequency region, indicating that PCS has a lower charge transfer resistance, so that the electrolyte can be quickly stored and released to the electrode surface; while the electrochemical impedance spectrum in the medium frequency region provides information about the electrochemical reaction kinetics on the electrode surface. PCS-MnO2 is loaded with MnO2, and its impedance in the charge transfer process is larger. At the same time, its electrochemical impedance is greater than that of PCS.
[0144] Fig. 9 CV comparison diagram of PCS-MnO2 prepared in Example 1 at different scan rates. Fig. 9 As shown in Figure 2, with the increase of the scan rate, the redox peak in the CV curve is larger and the redox type is stronger, which confirms that the addition of Mn 4+ It is effective to increase the proportion of pseudocapacitance. 4+ Improving its electrochemical performance is a feasible approach.
[0145] Fig.10 The pseudocapacitance ratio of PCS-MnO2 prepared in Example 1 is shown in Figure 2. The pseudocapacitance ratio can be calculated according to Formula 2. Fig.10 It can be seen that with the increase of scanning speed, the proportion of pseudocapacitance increased from 59% to 85%, and the proportion of double-layer capacitance decreased from 41% to 15%, which also proved that the Mn 4+ The redox form increases the pseudocapacitive performance of porous carbon materials.
[0146] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, once those skilled in the art know the basic creative concept, they can make other changes and modifications to these embodiments, and these changes and modifications all fall within the scope of the present invention.
[0147] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. If these modifications and variations of the present invention fall within the scope of the equivalent technology of the present invention, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a MnO2-loaded porous carbon-based electrode material, characterized in that: The following steps are involved: Coal tar pitch is used as a carbon precursor, and a mixed salt of carbonate and chloride salt is used as an activator. The coal tar pitch and the activator are mixed, and the molten salt method is used to pyrolyze the coal tar pitch at high temperature to convert it into a carbon material. The activator forms pores in the carbon material. At the same time, the Cl in the chloride salt - Attaching to the carbon material to obtain a porous carbon material; The porous carbon material and potassium permanganate solution are mixed by an impregnation precipitation method, and the potassium permanganate is reduced to MnO2 under the action of a reducing agent and loaded on the porous carbon material to obtain a porous carbon-based electrode material loaded with MnO2.
2. The method for preparing a MnO2-loaded porous carbon-based electrode material according to claim 1, characterized in that: The mass of the activator is 1 to 5 times that of the coal tar pitch.
3. The method for preparing a MnO2-loaded porous carbon-based electrode material according to claim 1, characterized in that: Every 1g of the porous carbon material is loaded with 0.125mol to 0.25mol of MnO2.
4. The method for preparing a MnO2-loaded porous carbon-based electrode material according to claim 1, characterized in that: The potassium permanganate solution is prepared by dissolving potassium permanganate in water and mixing the mixture. The concentration of the potassium permanganate solution is 0.005 mol / L to 0.01 mol / L.
5. The method for preparing a MnO2-loaded porous carbon-based electrode material according to claim 1, characterized in that: The pyrolysis temperature is 700°C to 900°C.
6. The method for preparing a MnO2-loaded porous carbon-based electrode material according to claim 1, characterized in that: The dosage ratio of the reducing agent to the potassium permanganate solution in the potassium permanganate solution is 4 mL to 8 mL: 0.5 mmol to 1 mmol.
7. The method for preparing a MnO2-loaded porous carbon-based electrode material according to claim 1, characterized in that: The reducing agent is methanol or sodium borohydride.
8. A MnO2 loaded porous carbon-based electrode material obtained by the preparation method according to any one of claims 1 to 7.
9. Use of the MnO2 loaded porous carbon-based electrode material according to claim 8 in preparing a supercapacitor.
10. The use according to claim 9, characterized in that: The loaded MnO2 porous carbon-based electrode material is used as an electrode in a supercapacitor; The supercapacitor is prepared by the following steps: The MnO2-loaded porous carbon-based electrode material and the conductive agent are mixed, and then a binder is added dropwise, and the mixture is ground and mixed until it becomes a black viscous state to obtain an active slurry; The active slurry is coated on a current collector and dried to form an active material layer on the current collector to obtain an electrode sheet; Dissolve KOH in water to prepare an electrolyte; The electrode sheets are placed in an electrolyte to form a supercapacitor.